Verba Majemuk Leksikal Tematik dalam Bahasa Jepang dan Pemaknaannya - Novia Lutfi Susanti; Djodjok Soepardjo; Roni Roni (LP. Ma'arif Janggan Magetan, 2023)
The process of forming compound verbs in Japanese has different patterns and rules from Indonesian. Japanese compound verbs are formed by combining two verbs to form a new verb that carries a certain meaning. The process of combining two verbs lexically can be grouped into aspectual lexical compound verbs and thematic lexical compound verbs. This research focuses on thematic lexical compound verbs, and provides a descriptive explanation of the meanings that emerge as a result of the process of combining two verbs thematic-lexically. This research uses a qualitative descriptive method with an interpretive approach, with proportional random sampling data collection techniques using documentation methods. The results of this research show that the process of combining two verbs thematic-lexically to form a lexical thematic compound verb will give rise to new meanings that can be seen from the relationship between V1 and V2, namely the meaning of means of action, manner of motion/movement, cause-result, and parallel meaning.